Perspectives on the U.S.-Mexico Soccer Rivalry : Passion and Politics in Red, White, Blue, and Green - Kassing, Jeffrey W.; Meân, Lindsey J. (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This edited volume considers the U.S.-Mexico soccer rivalry, which occurs against a complex geo-political, social, and economic backdrop. Multidisciplinary contributions explore how a long and complicated history between these countries has produced a unique rivalry-one in which loyalties split friends and family; fan turnout in many regions of the U.S. favors Mexico; and games are imbued with both national pride and politics. The themes of nationhood, geography, citizenship, acculturation, identity, globalization, narrative and mythology reverberate throughout this book, especially with regard to how they shape place, identity, and culture.
Keywords: Social sciences.; Culture -- Study and teaching.; Sports -- Sociological aspects.; elektronické knihy; electronic books